Separation, Extraction and Purification of Natural Products from Plants (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This special issue "Separation, Extraction and Purification of Natural Products from Plants" contains high-quality multidisciplinary research and review articles on various aspects of natural products. Quality by design (QbD) is a science-based and risk-based concept. The implementation of QbD ensures consistent high quality of natural product. The advantages of the concept are reflected in the researches collected in this special issue, such as the two articles on the optimization of the steam distillation process from Jiangxi University of Chinese Medicine. Process analytical technology (PAT) is an important part of the implementation of QbD concept. Two articles from Dr. Li Wenlong combines spectroscopy and chemometrics, providing good examples on the monitoring of natural product preparation process. Chromatographic separation and analysis are very important for quality control of natural products. There are six articles from different countries focusing on this topic. There are two articles investigating separation technologies, including membrane filtration and ethanol precipitation. Traditional Chinese medicines are also an important category of natural products. A review from Zhejiang University talks about the quality control of Xiaochaihu Capsule. I received a lot of help from friends from universities and enterprises in completing this special issue. I would like to express my gratitude to them. My thanks also go to the editors of this journal of Separations.